Numerical study of Chemical and Radiation absorption on convective Heat and Mass Transfer through a porous medium In a Channel (International Journal of Food and Nutritional Sciences, 2022)
We analyse the effect of chemical reaction and radiation absorption on unsteady convective Heat and Mass Transfer flow of viscous fluid through a Porous Medium in a vertical channel in the presence of Heat generating sources. The unsteadiness in the flow is due to a traveling thermal wave imposed on the boundary y=+L. Taking the aspect ratio δ